Bagaimana Terbebas dari Rentenir? Upaya Pemberantasan Praktik Riba di Desa Pekarungan Kabupaten Sidoarjo - Nurul Fatma Hasan; Makrifatul Ilmi (Al-Maqashid: Journal of Economics and Islamic Business, 2022)
This study aims to reveal the profile of poverty and cases of entrapment of loan-shark in Pekarungan-Sukodono-Sidoarjo. This research also explores the efforts that need to be done so that the community can be free from loan-sharks. This study used descriptive qualitative method. The data analysis technique consists of the stages of data collection, data reduction, data presentation, and drawing conclusions and verification. The results of the study reveal that residents of Pekarungan-Sidoarjo who borrow money through loan-sharks are increasingly experiencing economic difficulties. Efforts that can be made in the context of releasing loan-sharks (poverty alleviation) are to increase zakat empowerment, increase the role of the Micro Waqf Board, and increase sharia financial inclusion.